Membangun ketahanan masyarakat terhadap stroke: edukasi, pendampingan dan pembentukan kader pencegahan Stroke - Isnawati, Nafisah; Agung C., Khrisna; Nuraini, April; Khoirun N., Hilda (Universitas Mataram, 2025)
Stroke is one of the diseases that causes the highest rates of death and disability in the world, including in Indonesia. This condition is often caused by preventable risk factors, such as hypertension, diabetes, high cholesterol, and unhealthy lifestyles. However, the low level of public understanding regarding risk factors and early symptoms of stroke has led to a high incidence of strokes that are not properly treated. Therefore, this community service activity aims to provide education on stroke prevention, recognizing early symptoms, and the importance of immediate treatment This activity was conducted through community health education sessions, basic health screenings such as blood pressure and blood sugar tests, and a campaign on the importance of a healthy lifestyle. The education focused on increasing public awareness of stroke warning signs and understanding stroke prevention and management. The results of this activity showed an improvement in the community's understanding of stroke risk factors and preventive actions that can be taken, as evidenced by pre-test and post-test results, which indicated a difference in knowledge before and after the activity.From the results of the community service participant characteristics, 76.3% were female, and the majority of participants fell into the young elderly category, aged between 66-74 years, accounting for 50.8%. The results of self-administered health tests showed that 28% of participants had normal levels, 18.6% had uric acid levels above normal, 5.1% had cholesterol levels above normal, and 6.8% had blood sugar levels above normal (prediabetes and diabetes). Blood pressure issues were found in 42.4% of participants, 84.7% were categorized as overweight according to their BMI, 67.8% had low muscle mass, 86.4% had high-risk visceral fat, 91.5% had high body fat, and 84.7% showed abnormalities in Basal Metabolic Rate (BMR) and body age.